CRUSTAL STRUCTURE AND IMPLICATIONS FOR THE TECTONIC EVOLUTION OF THE ARCHEAN WESTERN SUPERIOR CRATON FROM FORWARD AND INVERSE GRAVITY MODELING - Nitescu B.; Cruden A.R.; Bailey R.C. (My University, 2006)
The distribution of mass anomalies within the crust of the Archean Western Superior Province has been investigated with forward and inverse gravity modeling routines. The gravity models indicate that in most of the Western Superior Province, significant mass anomalies occur only within the top 10 km of the crust, where they are generally related to dense metavolcanic rocks and low-density granitoid plutons, and at the crust-mantle boundary, where they are linked to undulations of this interface. An exception is the region encompassing the central Wabigoon Subprovince and the segments of the Quetico and Wawa belts south of it, where implied large intracrustal mass anomalies are associated with a segment of denser lower crust, and with overlying depressions of the interfaces between the main crustal layers. We interpret the predominant lateral mass homogeneity observed at deep crustal levels as evidence of mass redistribution processes associated with a major postaccretionary episode of thermal softening of the Western Superior crust. The incongruent presence of a denser lower crustal segment may reflect the subsequent modification of the lower crust through magmatic intra and underplating, possibly in relation with the Mesoproterozoic midcontinent rifting event. Copyright 2006 by the American Geophysical Union.
Keywords: Archean; Mesoproterozoic; Precambrian::Archean; Докембрий::Архей; Precambrian::Proterozoic::Mesoproterozoic; Докембрий::Протерозой::Мезопротерозойская